2015
DOI: 10.1017/s1463423615000560
|View full text |Cite
|
Sign up to set email alerts
|

District nurses’ experiences of preventive home visits to 75-year-olds in Stockholm: a qualitative study

Abstract: This qualitative study included five group interviews with 20 DNs. Data were analysed with qualitative content analysis. Findings DNs' experiences of barriers to and facilitators of a successful health dialogue were sorted into five domains. Together, these domains provided a systematic description of the interaction between the DN and the older person in the PHV. The domains included: establishing trustful contact, conducting a structured interview, making an overall assessment, proposing health-promoting act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 35 publications
1
25
0
Order By: Relevance
“…Consistent with our findings, communication skills and building a positive relationship are seen by older people as a vital part of their services 191,193,194 and have been emphasised in other participatory design processes around frailty prevention. 195 Addressing cognitive, social, psychological and home environment dimensions within frailty prevention services have been advocated by stakeholders 170 and physical and occupational therapists.…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with our findings, communication skills and building a positive relationship are seen by older people as a vital part of their services 191,193,194 and have been emphasised in other participatory design processes around frailty prevention. 195 Addressing cognitive, social, psychological and home environment dimensions within frailty prevention services have been advocated by stakeholders 170 and physical and occupational therapists.…”
Section: Discussionsupporting
confidence: 89%
“…In Norway, structural barriers limit cooperation between PHV services and GPs, leading to missed opportunities for longitudinal PHV services with competent nurses to add the benefits of preventive measures for their users. was identified as essential in qualitative PHV studies 12,15,22 , as well as other interventions to older people 41,42 . The time for users to judge the nurses' personal and professional trustworthiness varied, and some users needed several visits before they engaged in constructive collaborations.…”
Section: Discussionmentioning
confidence: 99%
“…While early PHV interventions had a predominant focus on disease prevention 7,8 , later PHV reviews display a more varied and broader focus 6,9 . Recent studies demonstrate that Scandinavian PHVs often include disease prevention as well as support for various aspects of subjective health and coping, and thus reflect a comprehensive understanding of health and health promotion [10][11][12] . In Scandinavia, a common approach is to offer annual PHVs to a general population of older people after a model from Denmark, in which annual PHVs from the age of 75 were legislated from 1996 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…In 2006, the Executive Board of the Stockholm County Council decided to implement preventive home visits for 75-year-olds by DNs [7]. As the main responsibility of DNs is to prevent diseases and promote health in the population, preventive home visits were regarded as a natural part of the DNs' professional tasks [8]. A study that investigated the selfreported health conditions of 75-year-olds and effects before and after a preventive home visit by a DN showed that nearly 60% accept the offer of a preventive home visit.…”
Section: Introductionmentioning
confidence: 99%
“…This work takes place both at health-care centres and in the patients' homes, for example during preventive home visits to 75-year-olds [6,7]. During these one-hour visits, DNs aim to establish a trustful contact with the older person, conduct a structured interview, make an overall assessment of the person's health and environment, and propose health-promoting activities and follow-up measures as needed [8].…”
Section: Introductionmentioning
confidence: 99%